Gender Equality and Taxation Policies in the EU - Åsa Gunnarsson; Ulrike Spangenberg (Intereconomics, 2019)
The persisting gender differences in employment rates and patterns and gender gaps in unpaid care work, employment rates, income, old age security, poverty and wealth are all closely linked to the allocative and distributional outcome of tax regulations.
Keywords: 330